Optimization of the extraction of phenolic compounds from Globularia alypum L. - Zidelmel, Imane; Koribaa, Bakhti (Laghouat : Université Amar Telidji - Département des sciences de la matière, 2025)
In this study, we extracted polyphenols of the plant Globularia alypum L using ultrasonic extraction process. The use of Response surface Methodology multivariate method by Box-Behnken design allows us to optimize three variables (temperature, time and volume of methanol). In order to obtain the best yield of Total Phenolic Compounds TPC;as well as the best antioxidants activities for both DPPH and ABTS. The optimal TPC yield was observed at 45 °C, 20 min, and 35 mL, while maximum antioxidant activities for both DPPH and ABTS occurred near 50 °C and 25 min. A strong correlation was observed between TPC and DPPH activities, confirming the contribution of phenolic compounds to radical scavenging potential. ABTS showed a similar but slightly weaker correlation. Overall, these results highlight the importance of optimizing extraction parameters to maximize the recovery of bioactive phenolics and their associated antioxidant activities.